The ‘right to be forgotten’ and the right to freedom of expression and information-legal problems on the basis of the judgment of the Supreme Administrative Court of 9 February 2023 - Klimas, Anita Marta (Central European Academy Law Review, 2025)
According to Art. 17(3) of Regulation (EU) 2016/679 of the European Parliament and of the Council, the ‘right to be forgotten’ is not absolute and is excluded when data processing is necessary to exercise the right to freedom of expression and information. These freedoms are protected by Art. 11 of the Charter of Fundamental Rights. The content of this provision is consistent with the text of Art. 10 of the European Convention on Human Rights, which is a source of protection of freedom of expression under European law. The freedom to express one’s views and to obtain and disseminate one’s information is provided for in Art. 54 of the Constitution of the Republic of Poland. In this regard, the Supreme Administrative Court expressed its view in the judgment of 9 February 2023, assuming that the ‘right to be forgotten’ applies to online archival press materials, and making such publications available is not necessary to exercise the right to freedom of expression. Therefore, it is possible to request the removal of personal data from such materials. The problem that emerged on the basis of the judgment issued boils down to the fact that the court did not fully take into account that the press plays an important role in society and the function of the press is not only to inform about various events, but it also has an archival function. Following the reasoning of the court, the past could be falsified. This verdict changes the rules of the media, is dangerous for the press and can have a ‘chilling effect’ on publishers. In this context, it is important to analyse the court’s interpretation from the point of view of grammatical and teleological interpretation of the provisions, which may also lead to the conclusion that outdated press materials will be removed ‘ex officio’.